Fishes : a guide to their diversity - Hastings, Philip A.; Walker, H. J. (Harold Jack), 1950-; Galland, Grantly R., 1982- (University of California Press, 2014)
"This is a coursebook and reference guide for ichthyology courses that will also serve as a tool for ichthyologists, fisheries scientists, marine biologists, and vertebrate zoologists. It will cover the basic anatomy and diversity of all 62 orders of fishes, focusing on the distinguishing characteristics of approximately 180 of the most commonly encountered fish families. Each family will be diagnosed with easily observed characteristics and clear photos--many in color and from living specimens. This guide will be distinctive through the use of photographs of preserved specimens primarily from the Scripps Institution of Oceanography Marine Vertebrate Collection, supplemented by radiographs and additional illustrations of key characters. The goal is to give ichthyology students, fisheries scientists, marine biologists, vertebrate zoologists, and others with an interest or stake in the diversity of fishes a broad overview of the morphological diversity of fishes, arranged in a modern classification system. For students, it's a natural complement to primary ichthyology textbooks, which don't cover the breadth of morphological characteristics necessary to identify fish"--Provided by publisher